2020
DOI: 10.4103/gmit.gmit_77_19
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism and adenomyosis: A retrospective review

Abstract: Objectives: The objective of the study was to evaluate the incidence of venous thromboembolism (VTE) in patients who have been admitted for adenomyosis at our institute and describe their clinical characteristics and management. Materials and Methods: A retrospective review of the medical records of all patients who were admitted to the gynecology ward between January 2015 and August 2016 was conducted, and all patients who had adenomyosis were included in this study. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 12 publications
(12 reference statements)
1
17
0
Order By: Relevance
“…There were a few cases that had co-occurrence of thrombi in other organs: brachiocephalic artery occlusion in one case [4], renal infarction in three cases [4,13,14], and splenic infarction in one case [9]. It has been suggested that adenomyosis can cause coagulopathy [1]. In particular, cerebral infarction caused by coagulopathy due to adenomyosis seems to exhibit similarities to Trousseau's syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There were a few cases that had co-occurrence of thrombi in other organs: brachiocephalic artery occlusion in one case [4], renal infarction in three cases [4,13,14], and splenic infarction in one case [9]. It has been suggested that adenomyosis can cause coagulopathy [1]. In particular, cerebral infarction caused by coagulopathy due to adenomyosis seems to exhibit similarities to Trousseau's syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Uterine adenomyosis, a common disease in which endometrial-like tissue is formed in the myometrium, has been known to cause menstrual pain and menorrhagia, with reports showing a prevalence of approximately 20% among women. Uterine adenomyosis can induce venous thromboembolism in 12.2% of cases [1], during menstruation or hypercoagulation due to tissue factors [2], causing elevated levels of cancer antigen 125 (CA125) [3] associated with menstruation. It has been shown that hypercoagulability associated with uterine adenomyosis can cause cerebral infarction [4], or deep vein thrombosis [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hong et al (22) reported 5 patients with adenomyosis who developed pulmonary thromboembolism and/or deep venous thrombosis. However, there were no significant differences in the clinicopathological characteristics between VTE and non-VTE patients; thus, it was unclear whether there was a causal association between adenomyosis and thromboembolism (22).…”
Section: Reviews Of the Literature On Adenomyosis-associated Thromboe...mentioning
confidence: 99%
“…Hong et al (22) reported 5 patients with adenomyosis who developed pulmonary thromboembolism and/or deep venous thrombosis. However, there were no significant differences in the clinicopathological characteristics between VTE and non-VTE patients; thus, it was unclear whether there was a causal association between adenomyosis and thromboembolism (22). Some patients with adenomyosis with a history of cerebral infarction or pulmonary thromboembolism have been shown to have elevated levels of plasma TAT, SF, D-dimer and PIC, suggesting an increased predisposition to thromboembolic events (10).…”
Section: Reviews Of the Literature On Adenomyosis-associated Thromboe...mentioning
confidence: 99%